Pengaruh Peran Ganda (Multitasking) dan Stres Kerja Terhadap Efektivitas Kerja Karyawan Pada Pointcoffee Cabang Medan - Dandi Priambudi Halim; Resna Napitu; Elfina O.P Damanik (Economic Education and Entrepreneurship Journal, 2022)
This study aims to determine the effect of multiple roles (multitasking) and the effect of work stress on the work effectiveness of the Medan branch of Pointcoffee employees. This research was conducted using a quantitative descriptive method with interviews, questionnaires and documentation. The data analysis technique used is the research instrument test: validity and reliability test, classical assumption test, multiple linear regression analysis, t test, f test, R2. It can be concluded that the results of this study are as follows: 1) multiple roles (multitasking) have a positive effect on work effectiveness with a value of Y = 19.378 + 0.14 X1 + 0.89 X2; 2) work stress has a positive effect on work effectiveness. 3) It is known that the results of the dual role F test (multitasking) and work stress have a significant effect on work effectiveness with the value of Sig. 0.017b. 4. It is known that the results of the T-test of multiple roles (multitasking) have a significant effect on work effectiveness with a value of sig.0.009. And work stress has a significant effect on work effectiveness with a value of Sig.0.027. 5. It is known that the results of the R2 test have a correlation coefficient (r) of 0.113. This shows the relationship between multiple roles (multitasking) and job stress with employee work effectiveness at a very strong level. Keywords: Job stress, multiple roles (multitasking), work effectiveness.